Project-based learning as a means to promote learner autonomy in ESL Classroom / Sharina Saad...[et al.] - Saad, Sharina; Ibrahim, Syazliyati; Abdullah, Amelia (2019)
The increased of interest in learner autonomy is mainly due to the rapid growth of information technology and globalization. In addition, the idea of learner autonomy is entailed in the Malaysian Education Blueprint (MEB 2013-2025) which highlights the use of Autonomous Language Learning (ALL) to improve language proficiency among students. Outdated pedagogical and conventional educational methods are no longer relevant in preparing learners for thriving in the workplace, and a more self-directed and self-determined approach is needed. Educators today are tasked with developing lifelong learners who can survive and thrive in a global knowledge economy. Hence, project -based learning is seen as one of the ways an educator can use to promote learner autonomy in ESL classrooms. This study is to investigate how the process of projectbased learning activities affects students' behaviours as well as develops learner autonomy. In this study, the researcher reports the impact of project- based learning in teaching English language proficiency skills course for semester one diploma students. Twenty-two semester one Diploma students, majoring in Accountancy course was involved in video project work for over one semester. A self-assessment questionnaire was administered at the end of the course to assess their learner autonomy and their perceived gained from the project work. The results showed that the students gained a higher degree of learner autonomy, increased intrinsic motivation and boost their confidence in speaking publicly, after participating in project- work. The gain was largely due to increased self -decisions on learning.